1997
DOI: 10.1046/j.1365-313x.1997.00711.x
|View full text |Cite
|
Sign up to set email alerts
|

Construction of an ∼2 Mb contig in the region around 80 cM of Arabidopsis thaliana chromosome 2

Abstract: A method for construction of bacterial artificial chromosome (BAC) contigs from a yeast artificial chromosome (YAC) physical map is described. An approximately 2 Mb contig, consisting of two large BAC contigs linked by a small YAC, has been assembled in the region around 80 cM of Arabidopsis thaliana chromosome 2. Clones from this contig will facilitate gene isolation in the region and can be used directly as substrates for DNA sequencing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…SSR markers were used for anchoring and comparing the frames of soybean genetic and physical maps (Shultz et al 2007;Shoemaker et al 2008). A physical map of a *2 Mb BAC contig in the region around 80 cM of Arabidopsis thaliana chromosome 2 was constructed using SSR markers and BAC endsequences (Wang et al 1997). Advent of new technologies has not affected the use of microsatellites due to their cost effectiveness and use in large scale genotyping.…”
Section: Rubus Idaeusmentioning
confidence: 99%
“…SSR markers were used for anchoring and comparing the frames of soybean genetic and physical maps (Shultz et al 2007;Shoemaker et al 2008). A physical map of a *2 Mb BAC contig in the region around 80 cM of Arabidopsis thaliana chromosome 2 was constructed using SSR markers and BAC endsequences (Wang et al 1997). Advent of new technologies has not affected the use of microsatellites due to their cost effectiveness and use in large scale genotyping.…”
Section: Rubus Idaeusmentioning
confidence: 99%
“…1). Based on the analysis of 231 F 2 progeny, the pkl-1 mutation mapped to within 1.1 centimorgans of the SSLP marker GPA-1, which had been anchored on the physical map of chromosome 2 (21). Further analysis of the 231 F 2 progeny revealed that the AFLP markers E11M48 and E14M59 (15) flanked pkl-1 and were tightly linked (Fig.…”
Section: ϫ8mentioning
confidence: 99%
“…For cloning of genomic fragments of the LC-1 line, we developed a new BAC vector based on pBeloBAC11 (Wang et al 1997). The lacZ part of pBeloBAC11 was replaced by a sacB negative selection cassette, which was obtained by PCR (primer ''sacB_for'': TGTGAT CTCATGAACATCAAAAAGTTTGC and primer ''sacB_rev'' TTATGCTCTAGATTATTTGTTAACT GTTAATTG) from vector pIB279 (Blomfield et al 1991).…”
Section: Construction Of Pbelobac-hdmentioning
confidence: 99%
“…Subsequently the DNA solution was concentrated with Microcon concentrators, a Schematic drawing of the pBeloBAC-HD vector. The pBeloBAC-HD vector originates from pBeloBAC11 (Wang et al 1997) but contains several modifications. The loxP site and the EcoRI site in the vector backbone were removed and a modified multiple cloning site containing EcoRI, NotI and I-SceI sites was introduced.…”
Section: Modification Of Bac E11mentioning
confidence: 99%
See 1 more Smart Citation